Enhancing gliotoxins production in deep-sea derived fungus Dichotomocyes cejpii by engineering the biosynthetic pathway. (June 2023) - Ye, Wei; Liu, Taomei; Liu, Yuping; Li, Mengran; Wang, Shixin; Li, Saini; Zhang, Weimin
Graphical abstract: Highlights: The transcriptional mechanism for gliotoxin was illustrated in Dichotomyces cejpii. gliZ, gliG and gliN genes are essential for the biosynthesis of gliotoxin in D. cejpii . Overexpression of gliZ can enhance gliotoxin yield by 16.38 ± 1.36 fold in D. cejpii. Deletion of gliM gene can improve gliotoxin yield by 18.98 ± 1.28 fold in D. cejpii . The dual function of GliN for N-methylation and O-methylation was firstly proposed. Abstract: Gliotoxin can be developed as potent biopesticide. In this study, the positive transcriptional factor g liZ, glutathione-S transferase encoding gene g liG and gliN were firstly deleted by CRISPR/Cas9 system, which abolished the production of gliotoxin-like compounds in Dichotomomyces cejpii. CRISPR/dCas9 system targeting promoter of gliG was used to activate the biosynthetic genes in gli cluster. The overexpression of gliZ, gliN and gliG can significantly improve the yield of gliotoxin-like compunds. The gliotoxin yields was improved by 16.38 ± 1.36 fold, 18.98 ± 1.28 fold through gliZ overexpression and gliM deletion in D. cejpii FS110. In addtion, gliN was heterologously expressed in E. coli, the purified GliN can catalyze gliotoxin into methyl-gliotoxin. Furthermore, the binding sequences of GliZ in the promoters of gliG was determined by Dnase footprinting. This study firstly illustrated the transcriptional regulatory mechanism of DcGliZ for the gliotoxin biosynthesis in D. cejpii, and improved the yields of gliotoxins significantly in D. cejpii via biosynthetic approaches.